Para onde eu vou? orientação profissional como subsídio para as escolhas de concluintes do ensino fundamental - Souza, Angelica Ribeiro de (2023)
The professional choice in the lives of young people represents a moment of doubts and uncertainties, given the political and economic transformations that we are experiencing in contemporary times. In this process of choice, professional guidance can represent a path to a more conscious and assertive decision-making, where young people are given the opportunity to learn about professions, the job market, as well as the construction of their life project, as provided for in the general competencies of the National Common Curricular Base (BNCC). The research here presented aims to answer the following problem: How to help students graduating from elementary school to mature their inclinations and professional choices regarding the future entry into Integrated High School? To answer this problem, we built the following objective: To contribute, through Professional Guidance, to the maturation of the professional inclinations of students graduating from Elementary School who are interested in entering Integrated High School. The methodological path in the research was based on the qualitative approach inspired by the case study, using documentary research, focus group and observation through the pedagogical workshop for data construction. The data analysis was based on the Creswell Spiral where we guided its stages of organization, description and classification of the data into codes so that there was an interpretation and representation of them. The research was carried out with students graduating from Elementary School of a public school in Manaus, interested in entering Integrated High School, to verify their expectations and doubts about entering High School. As an educational product of the research, we developed a guide entitled "Career Guidance Guide: Navigating the Waters of Professional Choices" which had the same objective as the research itself. The results from the observation and analysis of the entire process showed the deficit regarding the previous knowledge of the research subjects about the next stage of basic education to be followed, whether it is propaedeutic high school or high school integrated with the technical or with the life project itself as a whole. Thus, we conclude that this study is relevant to science because it provides a basis for further studies and deepening of the desire to help young people still in Elementary School to design their future for the continuation of their life projects and continuity of studies.